1991
DOI: 10.1515/dmdi.1991.9.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Primary Screening and Inhibition of Macromolecular Biosynthesis in Ehrlich Ascites Cells by Benzo(c)fluorene Derivatives

Abstract: The main objective of the present investigation was to screen a series of new benzo(c)fluorene compounds for in vitro activity. It can be stated that each of the 9 newly synthesized benzo(c)fluorene derivatives was about 10 times as active as tilorone. To elucidate the biochemical mode of action, the effects of 2 new compounds (13468 and 14200) on biosynthesis of macromolecules indicated by the incorporation rate of [14C]adenine (DNA, RNA), [14C]-thymidine (DNA), [14C]uridine (RNA) and [14C]valine (protein) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…1A). R value less than one is characteristic for biologically active substances that interfere with energy metabolism cells directly or indirectly by affecting the integrity of biological membranes (Majtán and Drobnica, 1982;Miko et al, 1991;Miko and Devínsky, 1993a;Miko and Devínsky, 1993b). 1B).…”
Section: Resultsmentioning
confidence: 99%
“…1A). R value less than one is characteristic for biologically active substances that interfere with energy metabolism cells directly or indirectly by affecting the integrity of biological membranes (Majtán and Drobnica, 1982;Miko et al, 1991;Miko and Devínsky, 1993a;Miko and Devínsky, 1993b). 1B).…”
Section: Resultsmentioning
confidence: 99%
“…The cytostatic and cytotoxic effects of BF were also proved in the studies performed in vitro. Inhibition of cell proliferation was proved in HeLa and V/79 cells (Horáková et al, 1988), Ehrlich carcinoma cells and P388 leukaemia cells (Miko et al, 1989). As well, Soucek et al (1987) showed that BF had a significant cytostatic effect on nine human leukemic cell lines in vitro.…”
Section: Introductionmentioning
confidence: 97%
“…Early studies assessed the influence of BF on the cell metabolism, proliferation and cell membrane integrity. It was established that benfluron may influence cell membrane processes, as well as synthesis of proteins and nucleic acids (Miko et al, 1989). The final cytotoxic effect of BF is concentration-dependent and differs in various cell types.…”
Section: Introductionmentioning
confidence: 99%